Visibilità e vitalità delle lingue. Un’analisi linguistica del greko di Calabria attraverso la lente del Linguistic Landscape - Micali, Irene (Quaderni di linguistica e studi orientali, 2024)
This paper analyzes the Linguistic Landscape of Bova Superiore, a small village in southern Calabria where Italo-Greek (Greko) is still spoken. Place-naming practices are considered communicative acts, and the linguistic signs inserted in the public space highlight the richness of the linguistic heritage of communities and contribute to the symbolic construction of collective identities. Through a mapping of the contact between the languages that characterize the Linguistic Landscape of Bova Superiore, the present study aims to fill a knowledge gap by stimulating a reflection on the degree of visibility and vitality of Greko.